Significance of ichnofossils in high resolution sequence stratigraphy: Upper Maastrichtian, Kopeh-Dagh Basin, NE Iran - Torghabeh, A.; Mahboubi, A.; Moussavi-Harami, R.; Wilson, Moyra (University of Tehran, 2012)
This study shows that ichonology can be used to refine sequence stratigraphy as well as to interpret the depositional environment of the Kalat Formation (Upper Maastrichtian) in the Central Kopeh-Dagh Basin (NE Iran), Dareh-Gaz section. Field studies and petrography of these deposits led to recognize four lithofacies and nine subfacies that formed in the tidal flat (lithofacies A), lagoon (lithofacies B), shoal (lithofacies C), and open marine (lithofacies D) within a carbonate ramp system. Trace fossils in this succession consist of Psilonichnus quietis, Thalassinoides suevicus, Diplocraterion parallelum, Rhizocorallium jenense and Ophiomorpha isp. that are classified in the Psilonichnus ichnofacies and Thalassinoides suevicus, Diplocraterion parallelum, Rhizocorallium jenense, and Ophiomorpha isp. in the Cruziana ichnofacies. Based on lithofacies and ichnofacies analyses, two depositional sequences (DS1 and DS2) were identified, that are composed of transgressive and highstand systems tracts. The maximum flooding surface (MFS) in DS1 is characterized at the top of the bed containing Rhizocorallium jenense, while this surface in DS2 is recognized by Diplocraterion parallelum grading into Ophiomorpha isp. in similar lithofacies. This study is an example where ichnology provides additional support for high-resolution sequence stratigraphy in carbonate deposits. Moreover, our study demonstrates that trace fossils could be useful in identification of the MFS in similar lithofacies elsewhere.